A Refined Model of Stress–Diathesis Relationships in Mothers With Significant Depressive Symptom Severity. (May 2021) - Matsuda, Yui; Schwartz, Todd A.; Chang, YunKyung; Beeber, Linda S.
BACKGROUND: Mothers' depressive symptoms affect their children's growth as well as physical and mental well-being. Moreover, mothers of young children with developmental delay or disability (DD) tend to have higher depressive symptoms.AIMS: The purpose of this study was to examine associations between maternal depressive symptoms and number of children with DD among mothers with significant levels of depressive symptoms, while accounting for maternal diathesis factors and family stress factors.METHODS: This study was a secondary analysis of pooled baseline data collected from 2004 to 2012 in the northeastern and southeastern United States from three intervention studies to reduce depressive symptoms of mothers with young children ( n = 364). Multiple regression analyses were conducted to examine associations between maternal depressive symptoms and number of children with DD, followed by the post hoc pairwise comparison.RESULTS: In the model including family stress factors, we found a significant test for linear trend in the mean for maternal depressive symptoms across the number of children with DD ( F [1] = 4.3, p = .0388).CONCLUSIONS: Mothers who have multiple children with DD tend to experience higher depressive symptoms; thus, interventions are needed to help prevent these mothers from experiencing higher depressive symptoms or to reduce their current depressive symptoms. Both theory-based and strength-based interventions can target conflict management at the family level, reducing maternal depressive symptoms while improving mothers' self-efficacy, which would help mothers care for their own health, manage family conflict, and seek appropriate support to manage the children's medical and developmental needs.